2009
DOI: 10.3805/eands.2.34
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe epilepsy associated with 'triple pathology' of hippocampal sclerosis, focal cortical dysplasia and cavernoma in the ipsilateral frontal lobe

Abstract: The coexistence of hippocampal sclerosis (HS) and extrahippocampal lesions such as focal cortical dysplasia (FCD) and cavernoma (CA) in temporal lobe epilepsies (TLE) is termed 'dual pathology'. We report a case of TLE having 'triple pathology' of HS, FCD and CA in the ipsilateral frontal lobe. Using chronic subdural electrode recording, an interictal electrocorticogram (ECoG) demonstrated that the medial temporal lobe lesion and the FCD lesion exhibited independent paroxysmal discharges, while an ictal ECoG d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In other words, "dual pathology" was not noted. Dual pathology does not merely indicate the morphological coexistence of hippocampal sclerosis with an extrahippocampal lesion, but also indicates the pathophysiologi-cal mechanisms such as the phenomena of kindling and secondary hippocampal epileptogenesis [14]. In the present case, we postulate that CD initially caused the repeated seizures and that the hippocampus gained secondary and independent epileptogenesis without morphological changes.…”
Section: A B C D Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In other words, "dual pathology" was not noted. Dual pathology does not merely indicate the morphological coexistence of hippocampal sclerosis with an extrahippocampal lesion, but also indicates the pathophysiologi-cal mechanisms such as the phenomena of kindling and secondary hippocampal epileptogenesis [14]. In the present case, we postulate that CD initially caused the repeated seizures and that the hippocampus gained secondary and independent epileptogenesis without morphological changes.…”
Section: A B C D Discussionmentioning
confidence: 62%
“…The seizure semiology and findings of the interictal EEG and functional imaging such as FDG-PET and IMZ-SPECT [6,7] were consistent with those of TLE, although the MR lesions in the temporal lobe extended outside of the temporal lobe. In this situation, invasive video-intracranial EEG monitoring with subdural grids or depth electrodes may be indicated to aid localization of the epileptogenic zone [1][2][3]14]. However, placement of the intracranial electrodes in the deep-seated continuous lesion such as fornix was too invasive, and surgery for the TLE under the guidance of intraoperative ECoG [8] was selected.…”
Section: A B C D Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of ‘triple pathology’ in epilepsy patients was initially proposed by Maciunas et al (9) and Samura et al (10). Samura et al reported a case of TLE with the coexistence of HS, FCD and cavernoma (CA) (10).…”
Section: Discussionmentioning
confidence: 99%
“…These most commonly involve combinations of tumor and focal cortical dysplasia or hippocampal sclerosis and focal cortical dysplasia [7][8][9][10][11]. Only rare instances of triple pathology, where 3 potentially etiologic lesions coexist in the same patient, have been reported [12][13][14][15].…”
Section: Introductionmentioning
confidence: 95%